(untitled) (International Journal of Engineering and Computer Science, 2014)
The mobile nodes in MANETs dynamically change their topology and hence require an efficient mechanism to communicate with each other. There are several routing protocols proposed for MANET environment categorized as Non-Location Based routing protocols and Location Based routing protocols. Among all routing protocols the Location based routing protocols are preferred in MANET as they are more efficient in routing compared with the Non-Location Based routing protocols. Also the MANET is vulnerable to several kind of attack such as black hole attack, wormhole attack, Sybil attack, flooding attack, gray hole attack etc. The Wormhole attack is one of the stronger active attacks which are difficult to avoid/detect in any network in which the two or more attacker nodes tunnel the network traffic information between source and destination pair from one network to another in the network. In this paper we focus our study on two location based routing protocols ALERT and GPSR and their effectiveness measure against wormhole attack based on parameters like throughput,end-2-end delay ,packet delivery ratio, packet dropping ratio and normalized routing load. The performance analysis is done for 10,20,30,40 and 50 nodes using the network simulator (NS-2.35).A comparative study is represented on above parameters for all five scenarios.